Numerical Methods for Solving Nonlinear Equations - Berenguer, Maria Isabel; Ruiz Galán, Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint contains 10 articles which have been published in a Special Issue of MDPI's journal Mathematics titled, 'Numerical Methods for Solving Nonlinear Equations', covering a wide range of topics on the numerical methods for solving nonlinear differential equations, nonlinear integral equations, nonlinear integro-differential equations, nonlinear variational equations, nonlinear optimization problems, nonlinear control problems, equilibrium problems or nonlinear algebraic equations.